Proceedings of the 2022 International Conference on Management of Data 2022
DOI: 10.1145/3514221.3517844
|View full text |Cite
|
Sign up to set email alerts
|

R2T: Instance-optimal Truncation for Differentially Private Query Evaluation with Foreign Keys

Abstract: If it is the author's pre-published version, changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In a subsequent work, Tao et al [38] use naive truncation to truncate the tuples with high sensitivity for self-join-free queries and they propose a mechanism to select 𝜏. However, our analysis (see the full version of our paper [15]) shows that the error of their mechanism is Ξ©(𝐺𝑆 𝑄 /log(𝐺𝑆 𝑄 )) with constant probability, i.e., it is at most a logarithmic-factor better than the naive Laplace mechanism that adds noise of scale 𝐺𝑆 𝑄 . We reduce the dependency on 𝐺𝑆 𝑄 from (near) linear to logarithmic.…”
Section: Related Workmentioning
confidence: 92%
“…In a subsequent work, Tao et al [38] use naive truncation to truncate the tuples with high sensitivity for self-join-free queries and they propose a mechanism to select 𝜏. However, our analysis (see the full version of our paper [15]) shows that the error of their mechanism is Ξ©(𝐺𝑆 𝑄 /log(𝐺𝑆 𝑄 )) with constant probability, i.e., it is at most a logarithmic-factor better than the naive Laplace mechanism that adds noise of scale 𝐺𝑆 𝑄 . We reduce the dependency on 𝐺𝑆 𝑄 from (near) linear to logarithmic.…”
Section: Related Workmentioning
confidence: 92%
“…User-DP is more general than tuple-DP, hence potentially incurring a higher privacy cost. Very recently, a logarithmic-neighborhood optimal mechanism has been proposed for CQs under user-DP [12]. Meanwhile, it has also been shown that 𝑂 (1)-neighborhood optimality is not achievable under user-DP [14] even for the simple query 𝑅 1 (π‘₯ 1 ) 𝑅 2 (π‘₯ 1 , π‘₯ 2 ) where 𝑅 1 is the primary private relation and 𝑅 2 .π‘₯ 1 is an FK referencing 𝑅 1 .π‘₯ 1 .…”
Section: Related Workmentioning
confidence: 99%
“…In actual implementation, we first compute 𝑇 Δ’ (I) for all 𝐸 βŠ† 𝐷 𝑖 , 𝐸 β‰  βˆ…. After that, it only takes 𝑂 (1) time to compute 𝑅𝑆 (I) using formulas (11), (12), and (13). Thus, the concrete computational complexity of 𝑅𝑆 (β€’) for a CQ π‘ž is 𝑂 (𝑁 𝑀 max ), where 𝑀 max is the maximum AJAR/FAQ width [3,21] of the residual queries of π‘ž.…”
Section: Computing 𝑅𝑆 (β€’)mentioning
confidence: 99%
See 1 more Smart Citation